The Differentiated Learning Strategy in Implementing “Merdeka Belajar” Curriculum of English Lesson in Junior High School - Widyastuti, Wiwin; Wiyanah, Sri (Universitas PGRI Yogyakarta, 2025)
Differentiated learning represents a key aspect of the independent curriculum, granting teachers the flexibility to select appropriate teaching methods. However, many teachers face challenges in implementing differentiated learning, and some still lack a clear understanding of its concept. Therefore, effective strategies are essential to enhance the teaching and learning process. This research aimed to explore the teaching strategies employed by teachers and analyze how they implement differentiated learning in English lessons. Using a qualitative approach with a case study design, the study involved two English teachers and two students as participants. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion verification. Data validity was ensured through source triangulation. The findings revealed that teachers utilized strategies such as motivation, brainstorming, ice-breaking activities, games, small group discussions, LRD (Listen-Read-Discuss), vocabulary drills, and demonstrations. For differentiated content, teachers incorporated books, videos, and the Merdeka Mengajar platform to vary learning materials. Differentiated processes were implemented by forming heterogeneous groups based on prior assessments. In terms of differentiated products, students were tasked with presenting worksheet results and writing essays following the teacher's instructions.